2019
DOI: 10.1080/16138171.2019.1693144
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic participation in Dutch amateur football clubs

Abstract: Sports, especially when organised within clubs, are often celebrated for their ability to link different ethnic groups together. However, various studies indicate the persistence of a gap between majority and ethnic minority sports participation. This study explores the participation of multiple ethnic groups in the Netherlands' most popular organised sport. Three explanations for ethnic disparities in sports participation are discussed and explored: a lack of resources, discrimination and ethnic specific spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Research has highlighted this inequality in multiple countries over time, such as Denmark (Agergaard et al, 2016), Finland (Zacheus, 2010), Germany (Burrmann et al, 2015), Norway (Strandbu et al, 2019), the Netherlands (Elling & Claringbould, 2005), and Switzerland (Buser et al, 2022). These findings underscore the need to understand the role of preferences, self-segregation, and collective exclusion mechanisms (Gomez-Gonzalez et al, 2021;van Haaften, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research has highlighted this inequality in multiple countries over time, such as Denmark (Agergaard et al, 2016), Finland (Zacheus, 2010), Germany (Burrmann et al, 2015), Norway (Strandbu et al, 2019), the Netherlands (Elling & Claringbould, 2005), and Switzerland (Buser et al, 2022). These findings underscore the need to understand the role of preferences, self-segregation, and collective exclusion mechanisms (Gomez-Gonzalez et al, 2021;van Haaften, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies of participation in sports clubs, however, overwhelmingly show that first- and second-generation immigrants, people from refugee backgrounds and other marginalized groups (e.g. Black and minority ethnic groups) are less likely to be members than their peers ( Elling and Claringbould, 2005 ; Feiler and Breuer, 2020 ; Higgins and Dale, 2013 ; Makarova and Herzog, 2014 ; Nielsen et al, 2013 ; van Haaften, 2019 ). While these findings might raise questions about potential discrimination in sport and thus conquer the great sport myth or the assumption about the integrative potential of sport, they seldom do so.…”
Section: Introductionmentioning
confidence: 99%
“…While these findings might raise questions about potential discrimination in sport and thus conquer the great sport myth or the assumption about the integrative potential of sport, they seldom do so. Instead, common explanations for the lower participation rates of immigrants and minority ethnic groups include cultural differences, socioeconomic disadvantages, different leisure preferences, and self-exclusion ( Burrmann et al, 2017 ; Higgins and Dale, 2013 ; Kleindienst-Cachay, 2007 ; Mutz and Burrmann, 2015 ; Nielsen et al, 2013 ; Spaaij, 2012 ; van Haaften, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of sports sociological studies have explored links between ethnicity and sports participation quantitatively, but it remains unclear how and/or with whom these activities are organized (e.g. Breuer & Wicker, 2008;Van Haaften, 2019). Furthermore, McPherson and his colleagues have demonstrated a positive relation between membership and shared similarities with co-members, but ethnicity was not included in these analyses (McPherson & Rotolo, 1996;.…”
Section: Sports Clubs: Sites For Interethnic Mixing?mentioning
confidence: 99%
“…Of these voluntary sports organizations, amateur football clubs are by far the most popular, accommodating well over a million members nationally. Moreover, earlier studies have shown that amateur football, unlike various other organized sports, enjoys a wide interest and high participation rates across various ethnic minority groups Van Haaften, 2019), illustrating its suitability as a case for both the study of ethnic homophily and sports' integrative potential. Consequently, I have formulated the following research question:…”
Section: Sports Clubs: Sites For Interethnic Mixing?mentioning
confidence: 99%